EXISTING TRENDS IN FOREIGN EXCHANGE RATES OF KENYA’S MAIN TRADING CURRENCIES - Obura, Ouma Johnmark; Mukras, M. S.; Oima, David (European Scientific Journal, ESJ, 2013)
﻿Performance of a security market reflects the economic situation of a country as it is affected by both a country’s domestic and foreign economic events. Given the current increased level of cross borders transactions with the value of total exports growing by 25.6% between 2007 and 2008 and imports increasing by 27.4% between the same periods, it was likely that fluctuations in foreign exchange rate market continued to fuel changes in financial markets like Nairobi Securities Exchange market. Since securities markets trade on assets with varying degree of risks, foreign exchange rates fluctuations was believed to be a factor that affect the performance of financial markets. The purpose of this study was to determine the trend of foreign exchange rates fluctuation of Kenya’s main trading currencies, the US Dollar, the Euro and the UK Pound. The study used secondary data collected between the periods January, 2006 to December, 2010 from the Central Bank of Kenya website in establishing the existing trend of foreign exchange rates fluctuation in Kenya. Descriptive statistics, Pearson Product Moment Correlation and Trend Analysis were used in the study. The findings revealed the existence of positive trends in US dollar and the Euro exchange rates and negative trends in UK pound exchange rates. Therefore the study recommended that market players like corporate investors and investment mangers should closely monitor these trends as they are useful in predicting future financial market outcomes.